E-learning as a tool to improve the quality of education in quantitative subjects - Szymańska, Anna; Zalewska, Elżbieta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
In recent years there has been a lot of changes in higher education. They result, among others, from the introduction of modern information technologies and communications to academic life. Providing high-quality education is one of the primary responsibilities of universities, which is why it is imperative to monitor how new methods and tools affect the quality of education. The University of Łódź, to meet the expectations of students, prepared a project of studies “E-Economics studies without barriers”. The main aim of this article is to present the project E-Economics studies without barriers and the evaluation of the course, including quantitative subjects, from the point of view of students and lecturers.
Didactics of Mathematics, 2015, Nr 12 (16), s. 125-134
Keywords: e-learning; higher education; quality education